UPGRADING GROWTH, YIELD, AND FOLATE LEVELS OF LETTUCE VIA SALICYLIC ACID AND SPIRULINA, VERMICOMPOST AQUEOUS EXTRACTS - Aseel M.H. H. Al-Khafaji,; Kadhim D. H. Al-jubouri, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The aim of this study is evaluating the impact of salicylic acid and Spirulina algae, vermicompost aqueous extracts, on lettuce (Lactuca sativa L.) traits. Field experiment was implemented at vegetable field of College of Agricultural Engineering Sciences - University of Baghdad during fall season 2021. The experiment was conducted using factorial arrangement within Randomized Complete Block Design with two factors and three replicates (3X3X3). Foliar spraying of salicylic acid represented the first factor (0, 150, 300 µmol.L-1), which symbolized (S0, S1, S2). The second factor was foliar application of distilled water, aqueous extracts of Spirulina (5g.L-1) and vermicompost (2:1 v/v) which symbolized (W, P, V) respectively. The results indicated the significance of interaction treatment S1P in producing the highest outer, inner leaves, head weight, folate content (24.67, 42.44, 916.7g, 142 µg.100 g-1 F.W.) respectively, in compare with control treatment S0W (15.33, 32.67, 550g, 96.3 µg.100 g-1 F.W.) respectively.